If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x(-10-2x)=0
We add all the numbers together, and all the variables
3x(-2x-10)=0
We multiply parentheses
-6x^2-30x=0
a = -6; b = -30; c = 0;
Δ = b2-4ac
Δ = -302-4·(-6)·0
Δ = 900
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{900}=30$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-30)-30}{2*-6}=\frac{0}{-12} =0 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-30)+30}{2*-6}=\frac{60}{-12} =-5 $
| x+6/7=+6 | | 3(x-5)=353x-5=35 | | x-19.4=14.1 | | 4b-17+12=b | | 0.06=x-1.95x | | 29-8x=x+5 | | 16+3b=b | | (5x+2)=6x | | 11y+6=86 | | 6x7=30+ | | 81=4r+5r | | 7c-3+2c=33 | | 60+n=114 | | 60+n=144 | | 10x-3x+x-2=14 | | 5n+18=+n | | 10f+2=8f+4 | | 10t+-13t−-14t+-1=10 | | 72=(-3t)-(-5t) | | 9(x-9)-3=-5(2x+4) | | 4+2x+3-x=2x-5 | | 2y+14=60 | | k=20-k | | -17k=17 | | 37-2w=25 | | 3k=20-4K | | 9s-8s+5=16 | | 5(1+4n)=85 | | 162+n=340 | | 162+n=34 | | 3D=20-4d | | 2x-10=47 |